2020
DOI: 10.1017/jog.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antarctic Peninsula glacier frontal ablation rates with respect to iceberg melt-inferred variability in ocean conditions

Abstract: Marine-terminating glaciers on the Antarctic Peninsula (AP) have retreated, accelerated and thinned in response to climate change in recent decades. Ocean warming has been implicated as a trigger for these changes in glacier dynamics, yet little data exist near glacier termini to assess the role of ocean warming here. We use remotely-sensed iceberg melt rates seaward of two glaciers on the eastern and six glaciers on the western AP from 2013 to 2019 to explore connections between variations in ocean conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Antarctic Peninsula (AP) glaciers (north of 70 • S) have the potential to raise the global sea level by 69±5 mm (Huss and Farinotti, 2014). In recent decades they have undergone extensive changes as a consequence of regional climate warming and oceanographic change (Cook et al, 2005(Cook et al, , 2014(Cook et al, , 2016Seehaus et al, 2018;Rott et al, 2018;Rignot et al, 2019;Dryak and Enderlin, 2020). As a complex mountainous coastal glacier system, the mass balance of the individual glaciers is affected by climate and oceanographic forcings and also by the subglacial and surrounding topography (Cook et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antarctic Peninsula (AP) glaciers (north of 70 • S) have the potential to raise the global sea level by 69±5 mm (Huss and Farinotti, 2014). In recent decades they have undergone extensive changes as a consequence of regional climate warming and oceanographic change (Cook et al, 2005(Cook et al, , 2014(Cook et al, , 2016Seehaus et al, 2018;Rott et al, 2018;Rignot et al, 2019;Dryak and Enderlin, 2020). As a complex mountainous coastal glacier system, the mass balance of the individual glaciers is affected by climate and oceanographic forcings and also by the subglacial and surrounding topography (Cook et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They have been derived from satellite radar altimetry (Helm et al, 2014;Li et al, 2017;Slater et al, 2018), laser altimetry (DiMarzio et al, 2007), a combination of both radar and laser altimetry Griggs and Bamber, 2009), optical photogrammetry (ASTER GDEM Validation Team, 2009Abrams et al, 2020;Howat et al, 2019), the combination of several sources of remote sensing and cartographic data (Liu et al, 2001;Fretwell et al, 2013), and single-pass synthetic aperture radar (SAR) interferometry of the TanDEM-X mission (German Aerospace Center DLR, 2018). In addition, regional DEMs of the marginal areas of the ice sheet have been generated from stereoscopic data (Korona et al, 2009;Fieber et al, 2018). An overview table with the parameters of the AP DEMs can be found in Table S1 of the Supplement.…”
Section: Introductionmentioning
confidence: 99%
“…The release of relatively cold fresh water facilitates sea ice growth (Bintanja et al, 2015;Merino et al, 2016), immediately lowers the sea surface temperature (Merino et al, 2016), and has been found to even influence ocean water down to 1500 m depth (Helly et al, 2011), as well as lead to upwelling of deep ocean properties (Jenkins, 1999). In terms of nutrients, icebergs have been shown to be the main source of iron in the Southern Ocean (Laufkötter et al, 2018;Raiswell et al, 2016;Wu and Hou, 2017) and therefore foster primary production in the proximity of icebergs (Biddle et al, 2015;Duprat et al, 2016;Helly et al, 2011), which in turn increases the abundance of krill and seabirds (Joiris, 2018;Smith et al, 2007) around icebergs. Furthermore, a range of studies have demonstrated that including more realistic iceberg distributions, trajectories, and volumes in climate models leads to a redistribution of fresh water and heat flux, which agrees better with observations than models that only include small icebergs or that treat iceberg discharge as coastal runoff (Jongma et al, 2009;Martin and Adcroft, 2010;Rackow et al, 2013;Schloesser et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The full freeboard of an iceberg can be estimated using the Digital Surface Model (DSM) generated using automatic image matching from optical stereo images. For example, Enderlin et al [25] and Dryak et al [26] used the DSM generated using WorldView satellite data to measure the freeboard and then the basal melting of icebergs. Li et al [27] generated a DSM covering an iceberg area in Prydz Bay using Unmanned Aerial Vehicle (UAV) optical images.…”
Section: Introductionmentioning
confidence: 99%